Peran Katekis Dalam Pertumbuhan Iman Anak Melalui Kegiatan BIAK - Elisabeth Yecilda Woga; Intansakti Pius X (Jurnal Silih Asah, 2024)
Catechists have an important responsibility in educating and guiding children to understand and live their spiritual life as Christians. This research uses the interview method to collect data. The research results show that catechists play a role as companions, directors and mentors in BIAK activities. Although some teaching responsibilities are transferred to students, the role of the catechist remains important in ensuring the quality of activities and supporting the successful teaching of the values of the Christian faith. One of the challenges faced by catechists is the lack of creativity in the learning process. This can be overcome by implementing learning methods and media that are interesting to children. This article concludes that collaboration between catechists and students is very important to achieve the goal of growing children's faith through BIAK activities. Catechists need to increase their creativity and ability to design interesting activities for children.